Synergistic mechanism between xanthan gum and locust bean gum: a perspective from hydrogen bonding, electrostatic, and hydrophobic interactions - Yantao Liu; Conghui Feng; Diming Li; Junxian Hu; Manyi Tu; Wei Xu; Pengfei Li; Zhoujian Xie; Liang He; Katsuyoshi Nishinari; Nan Yang (Food Hydrocolloids, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Corn stalk as a green reductant for leaching of low-grade copper-cobalt oxide ore: Hydrolysis and leaching performance - Faxin Xiao; Yaru Zhao; Xiaoni Shen; Jipeng Liu; Hui Li; Wei Xu; Shuchen Sun; Ganfeng Tu; Bencheng Xu (Minerals Engineering, 2026)

Real-time deformation monitoring of long-span bridges by coupling computer vision with inertial measurement - Chen Ruizhe; Tu Wei; Li Qingquan; Yuan Zhibin; Chen Zhipeng; Zhang Bochen; Hua Yuansheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Distribution of per- and polyfluoroalkyl substances in renal vascular tissues from donors after brain death and association with post-transplant delayed graft function risk - Dazheng Li; Tianyi Wang; Wenxiu Zhang; Yunchao Wang; Xianduo Li; Wei Chen; Sheng Tu; Dongdong Chen; Jianning Wang; Wenzhi Du (Environmental Pollution, 2026)

Antagonistic effects of PM2.5 and ozone on respiratory morbidity: A multi-pollutant interaction analysis using outpatient data from China's Pearl River Delta - Shui-Yue Lu; Xue-Dan Xu; Dao-Qin Wang; Muhammad Amjad; Guang-Hui Dong; Li-Zi Lin; Hong-Wei Tu (Atmospheric Environment, 2026)

The phyllosphere as a potential microbial habitat sharing taxa with the Jiang-flavor Baijiu fermentation system: A preliminary study - Fangzhou Li; Siyuan Wang; Bi Chen; Min He; Jianguo Zhou; Guilan Duan; Yongguan Zhu; Wei Liu; Huabin Tu (Food Research International, 2026)

Cod protein modifications induced by lipid oxidation-derived aldehydes: Insights into multi-aldehydes environment - Ting-qi Yang; Shenghai Liu; Kaiyu Jiang; Juncai Tu; Menghui Wang; Yuxuan Liang; Jinjin Li; Beiwei Zhu; Wei Gong (Food Chemistry, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Impact of the coupling effect between topographic factor and tillage disturbance on slope morphological evolution and soil redistribution - Ziting Ma; Yong Wang; Dandan Li; Xiaoman Tu; Xingcheng You; Hongtao Chen; Wei Qin; Haichao Xu (Journal of Soils and Sediments, 2026)

Discovery of a Novel Alloherpesvirus in Diseased Turbot in China - Wenli Liu; Qihang Tu; Yueqi Wu; Jing Li; Wei Lin; Fengjuan Tian; Wenguang Xu; Shan Xu; Yigang Tong (Journal of Fish Diseases, 2026)

Prospective life cycle assessment for high-value hydrogen from plastic waste by catalytic microwave processing: from laboratory to industrial scale - Zihao Shi; Zhenzhen Hong; Mengying Chen; Mulan Tu; Chuanping Li; Fen Wei; Xiong Peng; Xiaochuan Chen; Junxiong Wu; Yuming Chen; Qinghua Chen; Wei-Qiang Chen; et al. (Resources, Conservation and Recycling, 2026)

Multifaceted assessment of recent saltwater intrusion along China’s coasts - Nan Xu; Zihao Zhang; Hao Xu; Jiaqi Yao; Hui Lu; Wenjia Cai; Yifu Ou; Hong Luan; Peng Gong; Wei Tu; Qingquan Li (Science Bulletin, 2026)

Targeting eIF5A2 hypusination with bikinin sensitizes hepatocellular carcinoma to lenvatinib by suppressing TFEB-mediated autophagy - Shuqian Wang; Qingyun Zhou; Qiaomei Lin; Shufen Zhang; Ying Cai; Fangnan Wu; Fangyuan Kuang; Lianghui Wang; Shangzhi Xie; Jiahua Lan; Li Zheng; Guodong Xu; et al. (Human Cell, 2026)

Effect of thalidomide on sporadic central nervous system arteriovenous malformations - Jiaxing Yu; Hongyun Zhang; Shiju Zhang; Tianqi Tu; Jingwei Li; Jian Ren; Shikun Zhang; Jing Chen; Gao Zeng; Chendan Jiang; Lisong Bian; Hao Peng; et al. (Science Bulletin, 2026)

Bioinspired hierarchical nanofibers enable molecular discrimination for environment-adaptive functionality integration - Yu Zhang; Shao-Zhen Wang; Zhuang Huang; Chang-Wei Zhang; Jia-Lian Gao; Shihang Li; Xiaoyu Chen; Kunkun Tu; Mengbao Fan; Boyu Du; Jiefeng Gao; Shenghui Zhang; et al. (Journal of Hazardous Materials, 2026)

Efficient hydrogen production from kitchen waste leachate in microbial electrolysis cell using spiral nickel mesh cathode under alkaline conditions - Lingli Tu; Shuyue Ma; Qingjuan Fan; Xin Li; Haiping Luo; Chunhai Wei; Guangli Liu (Journal of Environmental Chemical Engineering, 2026)

Influence mechanisms of biomass properties on pyrolysis activation energy revealed by stacked generalization meta-learning model - Zhuo Tu; Luping Tian; He Xu; Zhaofeng Chang; Wei Du; Peng Zhang; Hao Li; Yunjiang Yu (Biomass and Bioenergy, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

A chitosan-based composite scaffold as a bioactive strontium-delivery system mediating accelerated bone regeneration - Jiyang Zeng; Wei Li; Yawei Li; Zhiming Tu; Hong Ma; Yuliang Dai; Bing Wang; Hongbing Deng (Carbohydrate Polymers, 2026)

Metagenomic and amplicon sequencing reveal the species distribution characteristics of the critically endangered Hucho bleekeri in wild and farmed environments - Yeyu Chen; Hua Li; Qinyao Wei; Zhao Liu; Yanling Chen; Yi Yu; Quanyu Tu; Guiliang Liu; Yan Liu; Huanchao Yang (Conservation Genetics Resources, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Remote sensing enables rapid assessment of the March 28, 2025 Myanmar earthquake - Nan Xu; Zihao Zhang; Qingquan Li; Yifu Ou; Wei Tu; Chao Yang; Chuanhua Zhu; Peng Gong; Hui Lu; Deliang Chen (Science Bulletin, 2026)

Metagenomic insight reveals the microbial structure and function of nitrous oxide emission from agricultural ditches - Zhangmu Jing; Qingqian Li; Shengqiang Tu; Yanjie Wei; Peng Yuan; Xiaoling Liu; Hongjie Gao (Journal of Hydrology, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

A large-scale framework for deriving tidal flat topography from SWOT data - Hao Xu; Nan Xu; Wenyu Li; Kai Tan; Chunpeng Chen; Huan Li; Lucheng Zhan; Pei Xin; Jiaqi Yao; Peng Li; Zhen Zhang; Haipeng Zhao; et al. (Remote Sensing of Environment, 2026)

Involvement of AcWRKY22 in nitric oxide-induced kiwifruit resistance against Botryosphaeria dothidea by regulating NO synthesis and phenylpropanoid pathway - Xiaoxia Zuo; Yangcheng Li; Jing Yang; Guiqing Tu; Jing Wang; Zhipeng Cai; Yonggen Shen; Huaying Du; Wei Zhang; Liqin Zhu (Postharvest Biology and Technology, 2026)

Transforming mine dump waste soil into biogeo-composites with vegetation growth regulation function through bio-mediated treatment - Zhile Wang; Guifang Zhang; Xiang Lu; Rongbo Lei; Wei Zhou; Yu Tian; Yu Lu; Lixiao Tu; Shiyuan Li (Journal of Hazardous Materials, 2026)

Constructing a hierarchical hydro-confinement network for strong, water-retaining, and multifunctional soybean flour adhesives - Qiangsong Jiang; Zechang Wei; De Li; Yongning Tu; Xiaohong Yu; Zhinan Wang; Hong Lei (Chemical Engineering Journal, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.

Brain functional basis of the association between positive expectation and acupuncture efficacy in knee osteoarthritis - Ze-Yi Wang; Cun-Zhi Liu; Xiao-Ya Wei; Na Zhang; Jin-Ling Li; Chihkai Lee; Hang Zhou; Jian-Feng Tu; Xu Wang (Brain Imaging and Behavior, 2026)

Stability of water-resistant rock mass of fault tunnels under high-temperature and high-pressure conditions - Chengping Zhang; Shiqin Tu; Tongxin Liu; Wei Li (Transportation Geotechnics, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Assessing nighttime homeless shelter accessibility and its socioeconomic associations in Los Angeles - Shengao Yi; Xiaojiang Li; Lehan Wang; Wei Tu; Qinyu Cui; Yatao Zhang; Xiana Chen; Tianhong Zhao (Journal of Transport Geography, 2026)

Tailoring pore architecture and functionality in COF-based mixed-matrix membranes for high-efficiency CO₂ capture - Linsheng Wei; Junda Dong; Yanshu Lu; Wenlin Zhou; Xing Chen; Wenfeng Tu; Jincheng Li; Binchun Zou; Guoji Huang (Journal of Environmental Chemical Engineering, 2026)

UrbanMMCL: Urban region representations via multi-modal and multi-graph self-supervised contrastive learning - Jinzhou Cao; Jiashi Chen; Xiangxu Wang; Weiming Huang; Dongsheng Chen; Tianhong Zhao; Wei Tu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Linking Sidescan Sonar Backscatter Intensity to Seafloor Sediment Grain Size Fractions: Insight from Dongluo Island - Songyang Ma; Bin Li; Peng Wan; Chengfu Wei; Zhijian Chen; Ruikeng Li; Zhenqiang Zhao; Chi Chen; Jiangping Yang; Jun Tu; Mingming Wen (Journal of Marine Science and Engineering, 2026)
Accurate characterization of seafloor sediment properties is critical for marine engineering design, resource assessment, and environmental management. Sidescan sonar offers efficient wide-area mapping capabilities, yet establishing robust quantitative relationships between acoustic backscatter intensity and sediment texture remains challenging, particularly in heterogeneous coastal environments. This study investigates the correlation between sidescan sonar backscatter intensity and sediment grain size parameters in waters southwest of Hainan Island, China. High-resolution acoustic data (450 kHz) were acquired alongside surface sediment samples from 18 stations spanning diverse sediment types. Backscatter intensity, represented by grayscale values, was systematically compared with grain size distributions and individual size fractions. Results reveal that mean grain size shows no meaningful correlation with backscatter intensity; however, fine sand fraction content (0.075–0.25 mm) exhibits a strong negative linear relationship (R2 = 0.87 under optimal conditions). Distribution-level analysis demonstrates that backscatter variability mirrors sediment textural complexity, with coarse sediments producing broad, elevated intensity distributions and fine sediments yielding narrow, suppressed distributions. Inter-survey variability highlights the sensitivity of absolute intensity values to environmental conditions during acquisition. Spatial distribution analysis reveals that sediment grain size follows a systematic NE-SW gradient controlled by hydrodynamic energy, with notable local anomalies controlled by reef structures (producing coarse bioclastic sediment) and topographic sheltering (maintaining fine-grained deposits in shallow areas). These findings provide a quantitative basis for fraction-specific acoustic classification approaches while emphasizing the importance of multi-scale analysis incorporating both regional hydrodynamic trends and local morphological controls. The established relationship between fine sand abundance and acoustic response enables semi-quantitative sediment prediction from remotely sensed data, supporting improved seafloor mapping protocols for offshore infrastructure siting, aggregate resource evaluation, and coastal zone management in morphologically complex environments.

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Identification of priority organophosphate esters and priority control areas based on toxic effects in the Taihu Basin, China - Xinyi Wang; Wei Jiang; Aimin Li; Yizhou Tu; Min Hu (Water Research, 2026)

Dual-anode electrochemical strategy enables simultaneous carbon and nitrogen removal from biologically treated landfill leachate - Zichao Lin; Hengyi Fu; Jianyi Zhou; Lele Tu; Qiaoxin Li; Rundong Chen; Li Tian; Wenxiao Zheng; Chaohai Wei; Chunhua Feng (Water Research, 2026)

Face stability analysis of horseshoe-shaped shield tunnels considering dynamic effects of composite cutterhead and screw conveyor - Junkang Lin; Shiqin Tu; Saixu Wang; Wei Li; Chengping Zhang (Tunnelling and Underground Space Technology, 2026)

Novel α-glucan phosphorylase coupled with thermotolerant yeast facilitated a high conversion rate from corn stover to artificial starch and microbial protein - Yanjun Li; Guoshun Xu; Jian Tian; Wangli Ji; Bo Liu; Tao Tu; Yuan Wang; Huoqing Huang; Huiying Luo; Bin Yao; Feifei Guan; Wei Zhang; et al. (Chemical Engineering Journal, 2026)

Coalescent 2D heterostructure for high-efficient surface-enhanced Raman scattering and electrochemical sensing - Muhammad H. Nawaz; S. Santhoshkumar; Thi H. Ho; Balamurugan Arumugam; Mohamed Gamal Mohamed; Tuan V. Vu; Yousra.M. Nabil; Mohammed G. Kotp; Li-Wei Tu; Hung-Duen Yang; Ahmed F.M. EL-Mahdy; Shiu-Ming Huang; et al. (Chemical Engineering Journal, 2026)

Face Failure Mechanism of Fault Tunnels in High-Energy Environments Based on 3D DFN-DEM Considering Thermo-Hydro-Mechanical Coupling Model - Tongxin Liu; Shiqin Tu; Chengping Zhang; Wei Li (Rock Mechanics and Rock Engineering, 2026)

Motor Cortex VIP Interneurons Participate in Dexmedetomidine-Associated Sleep Modulation - Wei Wang; Hanmei Zhang; Tianqi Zhang; Qianyi Huang; Jiaxin Li; Nuo Li; Yue Xi; Xiaohan Yang; Fen Wang; Jun Tu; Dongmei Ji; Juan Cheng (Molecular Neurobiology, 2026)

Planning for cooler cities: A multimodal AI framework for hyperlocal spatio-temporal urban heat stress prediction and mitigation - Shengao Yi; Xiaojiang Li; Wei Tu; Tianhong Zhao (Urban Forestry & Urban Greening, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Lateral dynamic response of bucket foundation in clay considering installation effect - Yufan He; Wenbo Tu; M. Hesham El Naggar; Xiaoqiang Gu; Yaoyu Jia; Lixiang Wei; Sen Li (Ocean Engineering, 2025)

Synergistic effect of self-assembled cinnamon essential oil-proanthocyanidin colloidal dispersion on in vitro starch and fat digestion - Zhihao Duan; Mianhong Chen; Yunxia He; Fanke Zeng; Hao Tu; Wei Zhou; Jihua Li; Ruyi Li (Food Chemistry, 2025)

Face stability of karst tunnels considering drag force of connected fracture based on limit analysis - Shiqin Tu; Wei Li; Chengping Zhang; Tongxin Liu (Computers and Geotechnics, 2025)

The Pilot Study on the Histological and Ultrastructural Characteristics of Major Immune Organs (Spleen, Head Kidney, and Trunk Kidney) and Analysis of Pathological Features in Sichuan Taimen ( Hucho bleekeri ) - Qinyao Wei; Hua Li; Yeyu Chen; Zhao Liu; Yanling Chen; Yi Yu; Quanyu Tu; Guiliang Liu; Zhaobin Song; Jun Du; Huanchao Yang (Journal of Fish Diseases, 2025)
Sichuan taimen ( Hucho bleekeri ) is a glacial relict and critically endangered fish species restricted to the Yangtze River drainage in China. The lack of knowledge regarding the morphology of immune organs may limit the timely detection of health threats, thereby hindering effective conservation efforts. To address this gap, the pilot study provides the first histological and ultrastructural characterisation of the main immune organs (spleen, head kidney, and trunk kidney) of H. bleekeri . The spleen comprises red and white pulp; the red pulp is abundant in erythrocytes, while the white pulp contains leukocytes within a reticular network. Melano‐macrophage centers, involved in immune and phagocytic activities, are prominent in the spleen and kidneys. The head kidney functions as a primary haematopoietic organ, exhibiting distinct lymphoid and non‐lymphoid zones supported by a reticular framework. The trunk kidney serves an excretory role, and its tissue contains dispersed renal corpuscles. Ultrastructural analyses revealed typical cellular features, including well‐developed rough endoplasmic reticulum and melano‐macrophage‐associated lysosomes. Notably, structural abnormalities—including mitochondrial swelling, cristae fragmentation, and mild dilation of the rough endoplasmic reticulum—were observed in the head kidney; these may potentially reflect early immune activation or sublethal environmental stress. These baseline findings would provide critical morphological references and lay a foundation for future studies on immune function, disease pathology, and conservation strategies in H. bleekeri .

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Clonal integration affects the responses of a rhizomatous dune plant to single severe and multiple shallow wind erosion events - Qing Wei; Yu-Kun Hu; Xiao-Lu Shen-Tu; Dan-Dan Li; Tian Li; Hai-Tao Miao; Shou-Li Li (Plant and Soil, 2025)

Environmental nano-particulates induced pre-implantation embryonic toxicity in pluripotent stem cell-derived blastoids - Gaojing Liu; Yayuan Li; Xiuyun Liu; Wei Wang; Xiao Wen; Yange Che; Qiu Tu; Bo Zhao (Environmental Pollution, 2025)

Atomized potassium-assisted hydrogen generation from ammonia decomposition over ruthenium loaded carbon-based catalysts - Qi Li; Hongfei Pan; Xiege Huang; Wei Xi; Wenmao Tu; Haining Zhang; Haolin Tang (Chemical Engineering Journal, 2025)

Integrated source apportionment and risk assessment prioritizes heavy metal control at an abandoned antimony smelter - Xiao-Hong Ma; Zhuan-Ling Shao; Yu-Han Wang; Wei-Di Tu; Li-Bang Ma; Jiao Wang (Environmental Geochemistry and Health, 2025)

Exploring the impact of processing temperatures on cod protein modifications by α, β-unsaturated aldehydes using a clickable probe - Kaiyu Jiang; Wei Gong; Yu-Xuan Liang; Juncai Tu; Jinjin Li; Weiman Gao; Xiuping Dong; Beiwei Zhu (Food Chemistry, 2025)

Efficient separation and quantitative sleep evaluation of phospholipids and glycerides of Antarctic krill - Yuxuan Liang; Kaiyu Jiang; Juncai Tu; Zhengqi Liu; Yuanyuan Hu; Wei Gong; Jinjin Li; Xiuping Dong; Gary Hardiman; Xiaoming Guo; Beiwei Zhu (Food Chemistry, 2025)

Quantifying seasonal bias in street view imagery for urban form assessment: A global analysis of 40 cities - Tianhong Zhao; Xiucheng Liang; Filip Biljecki; Wei Tu; Jinzhou Cao; Xiaojiang Li; Shengao Yi (Computers, Environment and Urban Systems, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Bottom-up structural analysis of amides by identifying collision-induced dissociation fragment ions: An application in bile acid-amino acid conjugates-targeted sub-metabolome profiling - Yuxuan Zhou; Wei Li; Xiaoya Niu; Yan Cao; Maodong Wang; Hangyun He; Zheng Cao; Qian Hong; Pengfei Tu; Yuelin Song (Analytica Chimica Acta, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Urban representation learning for fine-grained economic mapping: A semi-supervised graph-based approach - Jinzhou Cao; Xiangxu Wang; Jiashi Chen; Wei Tu; Zhenhui Li; Xindong Yang; Tianhong Zhao; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Enhanced biodegradation of sulfamethazine in swine manure composting: Pathway elucidation, mechanism insights, and optimization of a novel Bacillus sp. strain - Xiaojun Lin; Jingtong Li; Chunyan Chen; Zifeng Luo; Hongxing Tu; Yuwan Pang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jianfeng Huang; Jingwen Zeng; Jinrong Qiu (International Biodeterioration & Biodegradation, 2025)

Multi-level ROS regulation to activate innate and adaptive immune therapies - Ke-Ke Feng; Cheng-Lei Li; Yi-Fan Tu; Shi-Cheng Tian; Rui Xiong; Bai-Sheng Sa; Jing-Wei Shao (Chemical Engineering Journal, 2025)

Effects of exogenous and endogenous Mn on litter decomposition at different stages under continuous N addition in a subtropical forest - Shijia Wang; Qi Zhong; Wei Ma; Xueru Li; Liting Zhang; Shixing Zhou; Junxi Hu; Xinglei Cui; Congde Huang; Yang Liu; Lin Xu; Hongling Hu; et al. (Forest Ecology and Management, 2025)

Defect engineering of zinc-modified ZSM-5 zeolite catalysts for efficient aromatic synthesis from ethane and CO2 - Chunyan Tu; Hao Wang; Weiming Zhai; Chunting Liu; Wei Huang; Wenlin Li (Chemical Engineering Journal, 2025)

Modulating JAK2/STAT3 signaling by quercetin in Qiling Baitouweng Tang: a potential therapeutic approach for diffuse large B-cell lymphoma - Xin-Zhuo Zhan; Tian-Hua Wei; Chen Huang; Hui Yu; Xiao-Li Chen; Xiang-Tu Kong; Zhi-Hao Shang; Shan-Liang Sun; Meng-Yi Lu; Hai-Wen Ni (Molecular Diversity, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Dynamic Modeling and Experimental Validation of Shock Isolation Performance for Shipborne Stewart-Platform-Based Bumper - Yongqiang Tu; Haoran Zhang; Yintao Li; Wei Wang; Gang Lu; Hongwei Lin; Xinkai Chen; Yan Huang; Jianyu Fan (Journal of Marine Science and Engineering, 2025)
The Stewart-platform-based bumper plays a critical role in shipborne strap-down inertial navigation systems (SINSs), effectively mitigating shock-induced disturbances to ensure measurement accuracy. Dynamic modeling for the bumper under a huge impact is a key issue in predicting the shock isolation performance of the bumper. In this paper, the dynamic modeling of shock isolation performance for Stewart-platform-based bumpers under huge impacts is proposed and validated experimentally. Firstly, a model of a Stewart-platform-based bumper is established considering the geometric configuration and dynamic parameters of the bumper by calculating the Jacobian matrix, stiffness matrix, damping matrix and mass matrix. Secondly, an analytic simulation of the impact is presented based on the measured impact acceleration, and the impact force on the load is derived according to the non-displacement assumption in the impact stage. Then, the Lagrangian formulation was systematically applied to establish governing equations characterizing the six-degree-of-freedom (DOF) dynamics of the bumper, incorporating both inertial coupling effects and nonlinear shock energy dissipation mechanisms. Afterwards, dynamic equations were solved via the Runge–Kutta method to obtain the theoretical results. Finally, the proposed dynamic modeling and shock isolation performance analysis method was validated via impact experiments for the bumper.

High potential in synergizing the reduction of dissolved organic carbon concentration and carbon dioxide emissions for submerged-vegetation-covered river networks - Qingqian Li; Ruixia Liu; Zhangmu Jing; Yanjie Wei; Shengqiang Tu; Huibin Yu; Hongjie Gao; Peng Yuan (Journal of Environmental Sciences, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Online extraction-LC–MS/MS is an alternative imaging tool for spatial-resolved metabolomics: Mint leaf as a pilot study - Wei Li; Wenzheng Li; Luyao Ren; Wenhui Zhao; Yuxuan Zhou; Xiaoyun Li; Pengfei Tu; Wenjing Liu; Yuelin Song (Food Chemistry, 2025)

Tumor cell-derived N-acetyl-aspartyl-glutamate reshapes the tumor microenvironment to facilitate breast cancer metastasis - Jie Xia; Lixing Zhang; Wucheng Zhu; Juchuanli Tu; Xilei Peng; Qiaodan Deng; Siqin Li; Xueyan He; Haonan Dong; Cuicui Liu; Xian Chen; Jiahui Xu; et al. (Science Bulletin, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Enhancing the stability and heavy metal immobilization of co-pyrolysis biochar through biomass and red mud co-pyrolysis: A synergistic mechanism - Xinyao Li; Liangzhong Li; Zhichao Huang; Zhaofeng Chang; Zhuo Tu; Luping Tian; Wei Du; Hao Li; Peng Zhang; Bo Pan (Journal of Environmental Management, 2025)

Gravity gradient signal extraction based on time-frequency feature threshold method - Tao Jiang; Bohai Ke; Xiaobing Yu; Li Yu; Meng Yang; Ji Fan; Chenyuan Hu; Wei Feng; Huafeng Liu; Min Zhong; Liangcheng Tu; Zebing Zhou (Journal of Applied Geophysics, 2025)

DHMMF, a natural flavonoid, suppressed gastric cancer growth by inducing apoptosis and autophagy via up-regulation of MAPK/c-Jun and Atg3/LC3 signaling - Xiaonan Chen; Longyan Wang; Huiming Huang; Fei Wang; Yingying Tian; Xuejiao Wei; Peng Tan; Zhuguo Wang; Pengfei Tu; Zhongdong Hu; Jun Li (Food Bioscience, 2025)

Face failure mechanism of fault tunnels under high-temperature and high-pressure conditions using the discrete element method - Tongxin Liu; Chengping Zhang; Wei Li; Shiqin Tu; Libin Wang; Zixian Jin (Computers and Geotechnics, 2025)

Nighttime light imagery or mobile phone footprints: Which better reflects urban socio-economics at the grid level? A case study in the Pearl River Delta, China - Jinzhou Cao; Xianyu Cao; Wei Tu; Xiaoliang Tan; Tong Wang; Guanzhou Chen; Xiaodong Zhang; Qingquan Li (Computers, Environment and Urban Systems, 2025)

Erwinia aeris sp. nov., A Novel Bacterium Isolated from the Surface of an Ore in Hubei Province, China - He-Bao Guo; Hong-Tu Zhu; Yi-Fan Zhang; Fu Yang; Xiao-Tong Ma; Shi-Gui Li; Hai-Lei Wei; Xiao-Xia Zhang (Current Microbiology, 2025)

Bioactivity-guided isolation of potent inflammasome and mitochondria damage inhibitory diterpenoids from Orthosiphon wulfenioides - Wen-Chao Tu; Peng-Yun Yang; Xing-Jie Zhang; Yuan-Lin Kong; Bo Li; Hui-Juan Wang; Muhammad Aurang Zeb; Xiao-Li Li; Mei-Feng Liu; Wei-Lie Xiao (Phytochemistry, 2025)

Missing-linker defects of Ce-UiO-66 for enhanced radical scavenging efficiency and proton conductivity in proton exchange membrane fuel cells - Ziqiang Tu; Xuan He; Xing Du; Weixin Li; Daheng Wang; Wei Fang; Haijun Zhang; Hui Chen; Lei Zhao; Cheng Wang (Chemical Engineering Journal, 2025)

Hydrogen elimination via a wire mesh coated with Pt/Al2O3 - Shuaishuai Yuan; Chuandong Li; Xinqi Yao; Wei Yu; Lei Wang; Ronghui Shao; Hongxiang Zheng; Xinhai Yu; Shan-Tung Tu (Chemical Engineering Journal, 2025)

Contribution of PAHs and NACs to brown carbon light absorption in PM2.5 in Nanchang, Southern China - Hong Huang; Xiang Xu; Changwei Zou; Yiying Wu; Chunyi Wang; Jianlong Li; Xiang Tu; Wei Deng; Qiyuan Wang (Atmospheric Environment, 2025)

Lactobacillus acidophilus JYLA-126 Ameliorates Obesity-Associated Metabolic Disorders by Positively Regulating the AMPK Signaling Pathway Through the Gut-Liver Axis - Ping Li; Xia He; Enxu Feng; Jing Wei; Huaijun Tu; Tingtao Chen (Probiotics and Antimicrobial Proteins, 2025)

Channel Shortening-Based Single-Carrier Underwater Acoustic Communications in Impulsive Environment - Xingbin Tu; Zicheng Li; Yan Wei; Fengzhong Qu (Journal of Marine Science and Engineering, 2025)
Underwater acoustic (UWA) communication encounters significant challenges, including impulsive noise from breaking waves and marine organisms, as well as long-delay taps caused by ocean properties and high transmission rates. To address these issues, we enhance the channel estimation process by introducing iteratively reweighted least squares (IRLS) methods and propose an impulsive noise suppression algorithm. Furthermore, we analyze the inter-frequency interference (IFI) resulting from channel variability and implement IFI cancellation (IFIC) during iterative processing. Furthermore, an IFIC-based dual decision–feedback equalization (DDFE) algorithm is proposed for fast time-varying channels, enabling a considerable reduction in channel length and subsequent equalizer complexity. The proposed IFIC-based DDFE algorithm with impulsive noise suppression has been validated through sea trial data, demonstrating robustness against impulsive noise. Experimental results indicate that the proposed algorithm reduces click signal energy and significantly improves receiver performance compared to traditional DDFE algorithms. This research highlights the effectiveness of adapted UWA communication strategies in environments characterized by impulsive noise and long delay taps, facilitating more reliable UWA communication.

Extreme heat event influences the toxic impacts of nano-TiO2 with different crystal structures in mussel Mytilus coruscus - Shuaishuai Wei; Yiran Mao; Inna M. Sokolova; Zhuoqing Li; Li'ang Li; Malik Shahzaib Khalid; Zhihan Tu; Zhen Zhong; Menghong Hu; Youji Wang (Science of The Total Environment, 2024)

Acrolein scavengers and detoxification: From high-throughput screening of flavonoids to mechanistic study of epigallocatechin gallate - Kaiyu Jiang; Zhao Yin; Wei Gong; Yu-Xuan Liang; Juncai Tu; Xiaoya Tao; Zhengqi Liu; Yuanyuan Hu; Jinjin Li; Xiaoming Guo; Juanying Ou; Jie Zheng; et al. (Journal of Hazardous Materials, 2024)

Probabilistic analysis for excavation stability in spatially variable soil based on upper bound method - Zixian Jin; Chengping Zhang; Wei Li; Saixu Wang; Libin Wang; Shiqin Tu (Computers and Geotechnics, 2024)

Ancient genomic time transect unravels the population dynamics of Neolithic middle Yellow River farmers - Shiwei Li; Rui Wang; Hao Ma; Zheng Tu; Limin Qiu; Haodong Chen; Li Jiang; Yuezu Geng; Hai Liu; Jifeng Wang; Qu Shen; Li Jin; et al. (Science Bulletin, 2024)

The study on fracture response of cracked pipeline considering the Lüders effect - Wei Ren; Jian Shuai; Shengwen Tu; Yi Shuai; Yuntao Li; Zhiyang Lv (Ocean Engineering, 2024)

Towards SDG 11: Large-scale geographic and demographic characterisation of informal settlements fusing remote sensing, POI, and open geo-data - Wei Tu; Dongsheng Chen; Rui Cao; Jizhe Xia; Yatao Zhang; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Fabrication, characterization, and bioactivity of self-assembled carrier-free colloidal dispersions from Citrus × Limon ‘Rosso’ essential oil and tea polyphenols - Fangying Cheng; Mianhong Chen; Zhihao Duan; Ying Zou; Yunxia He; Fanke Zeng; Yuan Yuan; Tiaokun Fu; Hao Tu; Ruyi Li; Jihua Li; Wei Zhou (Food Chemistry, 2024)

Time-varying ambient air pollution exposure is associated with gut microbiome variation in the first 2 years of life - Tianlai Qiu; Qingbo Fang; Xuqi Tian; Yanan Cao; Xiaoxiao Fan; Yanting Li; Yiming Tu; Linxia Liu; Zitong Chen; Yi Wei; Jinbing Bai; Jing Huang; et al. (Environmental Pollution, 2024)

Valence electronic engineering of hollow-nanocube-structured CoFeNi-layered double hydroxides for highly efficient oxygen evolution - Lu Liu; Lingxing Zan; Yunchuan Tu; Hongling Zhang; Dan Zhu; Zhe Li; Jiawen Zheng; Zhuangzhuang Zhang; Yu Sun; Qiang Weng; Jian Li; Qingbo Wei; et al. (Chemical Engineering Journal, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

LCZ-based city-wide solar radiation potential analysis by coupling physical modeling, machine learning, and 3D buildings - Xiana Chen; Wei Tu; Junxian Yu; Rui Cao; Shengao Yi; Qingquan Li (Computers, Environment and Urban Systems, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Model test and discrete element method simulation of tunnel face stability in sand-gravel inclined layered stratum - Shiqin Tu; Wei Li; Chengping Zhang; Tongxin Liu; Libin Wang; Zixian Jin (Computers and Geotechnics, 2024)

Near-infrared-LED photostimulated luminescent nanoprobes based on lanthanide-doped SrS nanocrystals - Wei Lian; Qianqi Yang; Yuhan Liu; Datao Tu; Liangzhi Cai; Xiaoying Shang; Bowen Li; Ping Hu; Wei Zheng; Zhuo Chen; Xueyuan Chen (Chemical Engineering Journal, 2024)

Mapping of a novel locus Ra conferring extreme resistance against potato virus A in cultivated potato (Solanum tuberosum L.) - Wei Huang; Jie Zheng; Bihua Nie; Jiana Li; Ruhao Chen; Xianzhou Nie; Zhen Tu; Kyle Gardner; Jiaru Chen; Manhua Yang; Jingcai Li; Jianke Dong; et al. (Theoretical and Applied Genetics, 2024)

Simultaneously reducing the intensity and increasing the frequency of sand movements promotes the performance of Artemisia ordosica seedlings in dune environments - Li-Chen Tang; Xiao-Lu Shen-Tu; Qing Wei; Hai-Tao Miao; Shou-Li Li (Plant and Soil, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Mitigated N2O emissions from submerged-plant-covered aquatic ecosystems on the Changjiang River Delta - Qingqian Li; Huibin Yu; Peng Yuan; Ruixia Liu; Zhangmu Jing; Yanjie Wei; Shengqiang Tu; Hongjie Gao; Yonghui Song (Science of The Total Environment, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Differential intestinal effects of water and foodborne exposures of nano-TiO2 in the mussel Mytilus coruscus under elevated temperature - Shuaishuai Wei; Peng Xu; Yiran Mao; Yuntian Shi; Wei Liu; Saishuai Li; Zhihan Tu; Liming Chen; Menghong Hu; Youji Wang (Chemosphere, 2024)

Neonicotinoid insecticides and metabolites levels in neonatal first urine from southern China: Exploring links to preterm birth - Zixiong Tang; Zhiwen Su; Chunhong Jia; Xin Wei; Zhenni Zhu; Yifei Qi; Zhenyan Zhang; Linjie Yao; Haixin Tu; Xiaohui Huang; Qianqian Niu; Wenwen Sun; et al. (Journal of Hazardous Materials, 2024)

Remediation effectiveness of aging diesel-contaminated soil using thermochemical treatment: Soil microstructure transformation and reusability - Yuan Li; Chaoliu Tu; Mingli Wei; Lei Liu; Wenwei Zhang (Journal of Cleaner Production, 2024)

Identify organic contaminants of high-concern based on non-targeted toxicity testing and non-targeted LC-HRMS analysis in tap water and source water along the Yangtze River - Shaoqing Zhang; Liben Chou; Wenxuan Zhu; Wenrui Luo; Chi Zhang; Jingfan Qiu; Meishuang Li; Haoyue Tan; Jing Guo; Chang Wang; Keng Tu; Kefan Xu; et al. (Water Research, 2024)

One-pot eutectic molten salt synthesis of MXene-supported nanoscale zero-valent iron composites for efficient adsorption and reduction of uranium - HaoWei Tu; YanZe Wu; ZiJie Li; PengCheng Zhang; Cuilian Wei; LiYong Yuan; NanNan Wang; Lin Wang; WeiQun Shi (Chemical Engineering Journal, 2024)

Phytochemical investigation on Ginkgo biloba L. (Ginkgoaceae) and its chemotaxonomic significance - Muhammad Aurang Zeb; Wen-Chao Tu; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Partial collapse mechanism of a horseshoe-shaped tunnel face in layered soils - Saixu Wang; Chengping Zhang; Wei Li; Shiqin Tu; Libin Wang; Zixian Jin (Computers and Geotechnics, 2024)

Crop-Soil-Environment Benefits of Equivalent Carbon Input from Organic Amendments in Rice Production Ecosystems - Mingyu Wang; Xian Xiao; Weiwei Wei; Yuan Zhao; Qianqian Li; Xingguo He; Hao Cai; Baohua Tu; Zenan Wang (Journal of Soil Science and Plant Nutrition, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Mitigating growth-stress tradeoffs via elevated TOR signaling in rice - Wei Li; Jiaqi Liu; Zeqi Li; Ruiqiang Ye; Wenzhen Chen; Yuqing Huang; Yue Yuan; Yi Zhang; Huayi Hu; Peng Zheng; Zhongming Fang; Zeng Tao; et al. (Molecular Plant, 2024)

Seepage effect on progressive failure of shield tunnel face in granular soils by coupled continuum-discrete method - Shiqin Tu; Wei Li; Chengping Zhang; Libin Wang; Zixian Jin; Saixu Wang (Computers and Geotechnics, 2024)

Rapid marine degradable poly(butylene oxalate) by introducing promotion building blocks - Zhu Tu; Lizheng Wang; Ying Lu; Yang Li; Lin Sang; Yu Zhang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Stability analysis for excavation in frictional soils based on upper bound method - Zixian Jin; Chengping Zhang; Wei Li; Shiqin Tu; Libin Wang; Saixu Wang (Computers and Geotechnics, 2024)

Impacts of COVID-19 on urban networks: Evidence from a novel approach of flow measurement based on nighttime light data - Congxiao Wang; Zuoqi Chen; Bailang Yu; Bin Wu; Ye Wei; Yuan Yuan; Shaoyang Liu; Yue Tu; Yangguang Li; Jianping Wu (Computers, Environment and Urban Systems, 2024)

Development and experimental study of a scaled model for dust dispersion in fully-mechanized mining face - Wei Zhang; Sheng Xue; Qingyi Tu; Xingxing Xu; Fei Xing; Chao Li (Journal of Cleaner Production, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

Pleiotropic QTL Underlying the Dormancy and Reducing Sugar Content in Potato Tubers Uncovered by Conditional QTL Analysis - Jingcai Li; Wei Tu; Guilin Xiao; Tengfei Liu; Huoyun Chen; Wentao Tao; Bihua Nie; Botao Song (Potato Research, 2023)

PLCB1 Enhances Cell Migration and Invasion in Gastric Cancer Via Regulating Actin Cytoskeletal Remodeling and Epithelial–Mesenchymal Transition - Yulin Wang; Zhiyue Tu; Wei Zhao; Liping Wang; Jing Jiang; Lili Gu; Meng Li; Lujian Jiang; Yibin Wang; Yinglu Bi (Biochemical Genetics, 2023)

CYP72D19 from Tripterygium wilfordii catalyzes C-2 hydroxylation of abietane-type diterpenoids - Jie Gao; Lin Ma; Yuan Liu; Lichan Tu; Xiaoyi Wu; Jian Wang; Dan Li; Xianan Zhang; Wei Gao; Yifeng Zhang; Changli Liu (Plant Cell Reports, 2023)

Inhibiting mechanisms of metal ion complexation on photogenerated reactive intermediates derived from dissolved black carbon - Yi-na Tu; Wei Tang; Weilin Wu; Huaying Liu; Xiangfen Cui; Senlin Tian; Yingjie Li; Weidong Jiao (Chemosphere, 2023)

Simultaneous oxidization-adsorption for arsenic and antimony by biological Fe-Mn binary oxides (BFMO): The efficiencies and mechanism - Mengying Si; Wei Cao; Chunyu Ou; Guangyuan Tu; Weichun Yang; Qingzhu Li; Qi Liao; Zhihui Yang (Process Safety and Environmental Protection, 2023)

Numerical simulation study on the exhaust gas migration of fuel vehicles under an airflow field in the confined space of an underground coal mine - Gaofeng Shi; Sheng Xue; Qingyi Tu; Wei Zhang; Chao Li (Fuel, 2023)

Harnessing Ag2S quantum dots with immune adjuvant for NIR-II fluorescence imaging-guided sonodynamic immunotherapy of colon cancer - Yuanyuan Zhang; Yujie Zhang; Yonghong Li; Yuhan Fu; Yuanru Zhao; Wei Zhao; Runqing Li; Yao Xian; Kangsheng Tu; Feng Wu; Cheng Li; Yuzhu Hou; et al. (Chemical Engineering Journal, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

Intra-host mutation rate of acute SARS-CoV-2 infection during the initial pandemic wave - Kim El-Haddad; Thamali M. Adhikari; Zheng Jin Tu; Yu-Wei Cheng; Xiaoyi Leng; Xiangyi Zhang; Daniel Rhoads; Jennifer S. Ko; Sarah Worley; Jing Li; Brian P. Rubin; Frank P. Esper (Virus Genes, 2023)

MSGNet: multi-source guidance network for fish segmentation in underwater videos - Peng Zhang; Hong Yu; Haiqing Li; Xin Zhang; Sixue Wei; Wan Tu; Zongyi Yang; Junfeng Wu; Yuanshan Lin (Frontiers in Marine Science, 2023)
Fish segmentation in underwater videos provides basic data for fish measurements, which is vital information that supports fish habitat monitoring and fishery resources survey. However, because of water turbidity and insufficient lighting, fish segmentation in underwater videos has low accuracy and poor robustness. Most previous work has utilized static fish appearance information while ignoring fish motion in underwater videos. Considering that motion contains more detail, this paper proposes a method that simultaneously combines appearance and motion information to guide fish segmentation in underwater videos. First, underwater videos are preprocessed to highlight fish in motion, and obtain high-quality underwater optical flow. Then, a multi-source guidance network (MSGNet) is presented to segment fish in complex underwater videos with degraded visual features. To enhance both fish appearance and motion information, a non-local-based multiple co-attention guidance module (M-CAGM) is applied in the encoder stage, in which the appearance and motion features from the intra-frame salient fish and the moving fish in video sequences are reciprocally enhanced. In addition, a feature adaptive fusion module (FAFM) is introduced in the decoder stage to avoid errors accumulated in the video sequences due to blurred fish or inaccurate optical flow. Experiments based on three publicly available datasets were designed to test the performance of the proposed model. The mean pixel accuracy ( mPA ) and mean intersection over union ( mIoU ) of MSGNet were 91.89% and 88.91% respectively with the mixed dataset. Compared with those of the advanced underwater fish segmentation and video object segmentation models, the mPA and mIoU of the proposed model significantly improved. The results showed that MSGNet achieves excellent segmentation performance in complex underwater videos and can provide an effective segmentation solution for fisheries resource assessment and ocean observation. The proposed model and code are exposed via Github 1 .

LmFKBP24 interacts with LmEaster to inhibit the antifungal immunity of Locusta migratoria - Neng Zhang; Shiqian Feng; Saiya Duan; Yiting Yin; Hidayat Ullah; Hongmei Li; Undarmaa Davaasambuu; Shuhua Wei; Xiangqun Nong; Zehua Zhang; Xiongbing Tu; Guangjun Wang (Pesticide Biochemistry and Physiology, 2023)

Neonicotinoid insecticides and their metabolites: Specimens tested, analytical methods and exposure characteristics in humans - Haixin Tu; Xin Wei; Yanan Pan; Zixiong Tang; Renli Yin; Junhao Qin; Huashou Li; Adela Jing Li; Rongliang Qiu (Journal of Hazardous Materials, 2023)

Face stability analysis of tunnels in saturated soil considering soil-fluid coupling effect via material point method - Shiqin Tu; Wei Li; Chengping Zhang; Libin Wang; Saixu Wang; Yuanhao Zhao; Jinping Wu (Computers and Geotechnics, 2023)

Elucidating the role of T-cell exhaustion-related genes in colorectal cancer: a single-cell bioinformatics perspective - Wei Tu; Yan Tu; Chunhong Tan; Honghong Zhong; Sheng Xu; Jun Wang; Lv Huang; Ling Cheng; Haoguang Li (Functional & Integrative Genomics, 2023)

Adaptation mechanisms of the soil microbial community under stoichiometric imbalances and nutrient-limiting conditions in a subtropical nitrogen-saturated forest - Lingjun Qiu; Yunjie Li; Qi Zhong; Wei Ma; Yuxiao Kuang; Shixing Zhou; Gang Chen; Jiulong Xie; Hongling Hu; Yuqin Chen; Lihua Tu (Plant and Soil, 2023)

Insights into the release of triclosan from microplastics in aquatic environment assessed with diffusive gradient in thin-films - Si-Si Liu; Yu-Wei Jia; Xiao-Yuan Guo; Jian-Liang Zhao; Yue Gao; Andy J. Sweetman; Guang-Guo Ying; Li Xu; Chen Tu; Chang-Er Chen (Science of The Total Environment, 2023)

Manganese indicates root decomposition rates across soil layer, root order, and tree species: Evidence from a subtropical forest - Guantao Chen; Yu Sun; Yuqin Chen; Wei Ma; Qi Zhong; Yunjie Li; Lingjun Qiu; Shixing Zhou; Gang Chen; Jiulong Xie; Lihua Tu (Soil Biology and Biochemistry, 2023)

Selective extraction of gold from strong acid E-waste leachate through H+-triggered cascade reaction of thiolated β-cyclodextrin - Difan Fang; Feihu Bi; Liming Yang; Wenbin Hu; Zan Hua; Hanchen Wei; Changli Chen; Yunyun Tu; Penghui Shao; Min Li; Xubiao Luo; Guang Yang (Resources, Conservation and Recycling, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

A Carrier-Based Gardner Timing Synchronization Algorithm for BPSK Signal in Maritime Communication - Fengzhong Qu; Zhengchao Li; Minhao Zhang; Xingbin Tu; Yan Wei (Journal of Marine Science and Engineering, 2023)
Wireless communication at sea is an essential way to establish a smart ocean. In the communication system, however, signals are affected by the carrier frequency offset (CFO), which results from the Doppler effect and crystal frequency offset. The offset deteriorates the demodulation performance of the communication system. The conventional Gardner bit-synchronization algorithm performs timing synchronization on the baseband, but it fails to solve the problem of carrier frequency offset. In this paper, a carrier-based timing-synchronization Gardner algorithm was proposed. The algorithm performed error detection in the carrier signal to estimate the synchronization error in real time and the time-domain expansion in the passband signal. Based on the estimated expansion factor, the algorithm located the sampling points of the ideal signal and re-interpolated all the sampling points on the passband to recover the passband signal without Doppler. This algorithm can solve both the frequency shift and time-domain expansion caused by the Doppler effect without further CFO estimation and compensation, thus reducing the overall computational complexity of the system. The simulations showed that the proposed algorithm greatly improves the ability of the communication system to combat Doppler compared to the conventional Gardner algorithm. The algorithm is primarily designed for binary phase-shift keying (BPSK)-modulated signals under the additive white Gaussian noise (AWGN) channel and can be applied to various maritime communication scenarios.

Methods and experiments for collecting information and constructing models of bottom-layer contours in paddy fields - Tuanpeng Tu; Jie He; Xiwen Luo; Lian Hu; Pei Wang; Gaolong Chen; Li Tian; Dawen Feng; Zhimin Wang; Zhongxian Man; Weicong Li; Zhenghui Wei; et al. (Computers and Electronics in Agriculture, 2023)

Long non-coding RNA MSTRG.81401 short hairpin RNA relieves diabetic neuropathic pain and behaviors of depression by inhibiting P2X4 receptor expression in type 2 diabetic rats - Mengyun Sun; Mingming Zhang; Haoming Yin; Hongcheng Tu; Yuqing Wen; Xingyu Wei; Wenhao shen; Ruoyu Huang; Wei Xiong; Guodong Li; Yun Gao (Purinergic Signalling, 2023)

Study on the management efficiency of lanthanum/iron co-modified attapulgite on sediment phosphorus load - Yihe Qu; Li Zhao; Zhenghai Jin; Haoran Yang; Chengqi Tu; Feifei Che; Mohammad Russel; Xinshan Song; Wei Huang (Chemosphere, 2023)

Self-diffusion coefficient and sound velocity of Fe-Ni-O fluid: Implications for the stratification of Earth's outer core - Wei-Jie Li; Zi Li; Chong-Jie Mo; Zhe Ma; Xian-Tu He; Cong Wang; Ping Zhang (Physics of the Earth and Planetary Interiors, 2023)

Sources, distribution and decomposition of soil organic matter based on an effective biomarker in the pastoral areas of Zoige Plateau, China - Bin Wang; Tingqian Shan; Junjie Wang; Fuyang Huang; Wei Liu; Weiguo Tu; Sen Li; Qingsong Chen (Chemosphere, 2023)

Effect of inclined layered soils on face stability in shield tunneling based on limit analysis - Shiqin Tu; Wei Li; Chengping Zhang; Wen Chen (Tunnelling and Underground Space Technology, 2023)

Shear induced lift and rotation on MicroFiber deposition in low Reynolds number flows - Jiang Li; Jiawei Ma; Goodarz Ahmadi; Jingliang Dong; Wei Yang; Jiyuan Tu; Lin Tian (Journal of Aerosol Science, 2023)

Overexpression of LtuHB6 from Liriodendron tulipifera causes lobed-leaf formation in Arabidopsis thaliana - Lingmin Wei; Shaoying Wen; Jikai Ma; Zhonghua Tu; Shenghua Zhu; Xinyu Zhai; Huogen Li (Physiology and Molecular Biology of Plants, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Reduced Firing of Nucleus Accumbens Parvalbumin Interneurons Impairs Risk Avoidance in DISC1 Transgenic Mice - Xinyi Zhou; Bifeng Wu; Wenhao Liu; Qian Xiao; Wei He; Ying Zhou; Pengfei Wei; Xu Zhang; Yue Liu; Jie Wang; Jufang He; Zhigang Zhang; et al. (Neuroscience Bulletin, 2021)
A strong animal survival instinct is to approach objects and situations that are of benefit and to avoid risk. In humans, a large proportion of mental disorders are accompanied by impairments in risk avoidance. One of the most important genes involved in mental disorders is disrupted-in-schizophrenia-1 ( DISC1 ), and animal models in which this gene has some level of dysfunction show emotion-related impairments. However, it is not known whether DISC1 mouse models have an impairment in avoiding potential risks. In the present study, we used DISC1-N terminal truncation ( DISC1-N TM ) mice to investigate risk avoidance and found that these mice were impaired in risk avoidance on the elevated plus maze (EPM) and showed reduced social preference in a three-chamber social interaction test. Following EPM tests, c-Fos expression levels indicated that the nucleus accumbens (NAc) was associated with risk-avoidance behavior in DISC1-N TM mice. In addition, in vivo electrophysiological recordings following tamoxifen administration showed that the firing rates of fast-spiking neurons (FS) in the NAc were significantly lower in DISC1-N TM mice than in wild-type (WT) mice. In addition, in vitro patch clamp recording revealed that the frequency of action potentials stimulated by current injection was lower in parvalbumin (PV) neurons in the NAc of DISC1-N TM mice than in WT controls. The impairment of risk avoidance in DISC1-N TM mice was rescued using optogenetic tools that activated NAc PV neurons. Finally, inhibition of the activity of NAc PV neurons in PV-Cre mice mimicked the risk-avoidance impairment found in DISC1-N TM mice during tests on the elevated zero maze. Taken together, our findings confirm an impairment in risk avoidance in DISC1-N TM mice and suggest that reduced excitability of NAc PV neurons is responsible.

Dibenzocyclooctadiene lignans from Artemisia sieversiana and their anti-inflammatory activities - Xu-Dong Zhou; Chao-Xi Chen; Xi-Kang Zheng; Li-Min Gong; Ke-Wu Zeng; Wei Wang; Peng-Fei Tu (Journal of Natural Medicines, 2021)

The effect of land use change and soil redistribution on soil organic carbon dynamics in karst graben basin of China - Gaoyong Lan; Chun Liu; Hua Wang; Wei Tang; Xia Wu; Hui Yang; Linling Tu; Bill X. Hu; Jianhua Cao; Qiang Li (Journal of Soils and Sediments, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Microsatellite records for volume 13, issue 1 - Xiang-Yang Jia; Wei Li; Kristina M Ramstad; Bin Tu; Jun Yan (Conservation Genetics Resources, 2021)

Effects of the Lower Airway Secretions on Airway Opening Pressures and Suction Pressures in Critically Ill COVID-19 Patients: A Computational Simulation - Zhenglong Chen; Ming Zhong; Li Jiang; Nanshan Chen; Shengjin Tu; Yuan Wei; Ling Sang; Xia Zheng; Chunyuan Zhang; Jiale Tao; Linhong Deng; Yuanlin Song (Annals of Biomedical Engineering, 2020)

Correction to: LncRNA NONRATT021972 involved the pathophysiologic processes mediated by P2X7 receptors in stellate ganglia after myocardial ischemic injury - Lifang Zou; Guihua Tu; Wei Xie; Shiyao Wen; Qiuyu Xie; Shuangmei Liu; Guilin Li; Yun Gao; Hong Xu; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

A novel cross-sensor calibration method to generate a consistent night-time lights time series dataset - Ying Tu; Hanlin Zhou; Wei Lang; Tingting Chen; Xun Li; Bing Xu (International Journal of Remote Sensing, 2020)

Concentrations, Sources, and Potential Human Health Risks of PCDD/Fs, dl-PCBs, and PAHs in Rural Atmosphere Around Chemical Plants in Jiangsu Province, China - Wei Liu; Jing Zhao; Shen Xu; Guang-Bing Liu; Yong Tu; Peng Shi; Ai-Min Li (Bulletin of Environmental Contamination and Toxicology, 2020)

Geological Control of Fold Structure on Gas Occurrence and Its Implication for Coalbed Gas Outburst: Case Study in the Qinan Coal Mine, Huaibei Coalfield, China - Kaizhong Zhang; Liang Wang; Yuanping Cheng; Wei Li; Jin Kan; Qingyi Tu; Jingyu Jiang (Natural Resources Research, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

Study on manufacturing process of ancient Chinese bi-metallic bronze Ge - Bingjie Li; Xudong Jiang; Yin Tu; Jianguo Lv; Qiang Fu; Bei Wei; Tao Hu; Chunxu Pan (Archaeological and Anthropological Sciences, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Cloning, molecular characterization, and tissue differential expression of connective tissue growth factor (ctgf) of grass carp - Wen-Qian Pan; Jun-Peng Wang; Zhi-Han Tu; Tian Gan; Jing Hu; Jing Wei; Xiang-Jun Leng; Xiao-Qin Li (Fish Physiology and Biochemistry, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Land use and land cover classification using Chinese GF-2 multispectral data in a region of the North China Plain - Kun Jia; Jingcan Liu; Yixuan Tu; Qiangzi Li; Zhiwei Sun; Xiangqin Wei; Yunjun Yao; Xiaotong Zhang (Frontiers of Earth Science, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Characterization and mechanism of copper biosorption by a highly copper-resistant fungal strain isolated from copper-polluted acidic orchard soil - Chen Tu; Ying Liu; Jing Wei; Lianzhen Li; Kirk G. Scheckel; Yongming Luo (Environmental Science and Pollution Research, 2018)

Erratum to: Hypoxia Augments Increased HIF-1a and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Syun Hu; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2018)

The higher grain production, the more social deprivation? A case study of Henan province in traditional agricultural areas of China - Jun-bo Gao; Wei-feng Qiao; Yan-sui Liu; Yu-rui Li; Wei Tu; Yong-xian Zhang (Journal of Mountain Science, 2018)

Prenylated benzoic acid derivatives from the stem of Euodia lepta - Ming-Bo Zhao; Si-Xiang Zhou; Qing-Ying Zhang; Wei-Feng Wei; Ming-Hui Li; Jian-Yong Xing; Yong Jiang; Peng-Fei Tu (Natural Product Research, 2017)

MicroRNA-15b silencing inhibits IL-1β-induced extracellular matrix degradation by targeting SMAD3 in human nucleus pulposus cells - Liang Kang; Cao Yang; Huipeng Yin; Kangcheng Zhao; Wei Liu; Wenbin Hua; Kun Wang; Yu Song; Ji Tu; Shuai Li; Rongjin Luo; Yukun Zhang (Biotechnology Letters, 2017)

A comparative study of strontium-substituted hydroxyapatite coating on implant’s osseointegration for osteopenic rats - Zhou-Shan Tao; Bing-Li Bai; Xing-Wen He; Wei Liu; Hang Li; Qiang Zhou; Tao Sun; Zheng-Liang Huang; Kai-kai Tu; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Anticholinesterases and antioxidant alkamides from Piper nigrum fruits - Yanbei Tu; Yujiao Zhong; Hongjian Du; Wei Luo; Yaya Wen; Qin Li; Chao Zhu; Yanfang Li (Natural Product Research, 2016)

Hypoxia Augments Increased HIF-1α and Reduced Survival Protein p-Akt in Gelsolin (GSN)-Dependent Cardiomyoblast Cell Apoptosis - Yu-Lan Yeh; Wei-Jen Ting; Chia-Yao Shen; Hsi-Hsien Hsu; Li-Chin Chung; Chuan-Chou Tu; Sheng-Huang Chang; Cecilia-Hsuan Day; Yuhsin Tsai; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

LncRNA NONRATT021972 involved the pathophysiologic processes mediated by P2X7 receptors in stellate ganglia after myocardial ischemic injury - Lifang Zou; Guihua Tu; Wei Xie; Shiyao Wen; Qiuyu Xie; Shuangmei Liu; Guilin Li; Yun Gao; Hong Xu; Shouyu Wang; Yun Xue; Bing Wu; et al. (Purinergic Signalling, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Identification of rare variants in TNNI3 with atrial fibrillation in a Chinese GeneID population - Chuchu Wang; Manman Wu; Jin Qian; Bin Li; Xin Tu; Chengqi Xu; Sisi Li; Shanshan Chen; Yuanyuan Zhao; Yufeng Huang; Lisong Shi; Xiang Cheng; et al. (Molecular Genetics and Genomics, 2016)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A bioinformatics method for predicting long noncoding RNAs associated with vascular disease - JianWei Li; Cheng Gao; YuChen Wang; Wei Ma; Jian Tu; JunPei Wang; ZhenZhen Chen; Wei Kong; QingHua Cui (Science China Life Sciences, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

Impact of Effective Stress and Matrix Deformation on the Coal Fracture Permeability - Pinkun Guo; Yuanping Cheng; Kan Jin; Wei Li; Qingyi Tu; Hongyong Liu (Transport in Porous Media, 2014)

Expression of rolGLP-HV in E. coli and its Dual-Function for the Treatment of Diabetes and Thrombosis - Yaofang Zhang; Yiming Wei; Baicheng Ma; Kunyan Qiao; Zhihua Ma; Chong Li; Chao Ma; Yanli Ji; Zhen Dong; Junfeng Hao; Peipei Tu; Jian-Hong Zhu; et al. (International Journal of Peptide Research and Therapeutics, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Evaluation of the antioxidant effects of four main theaflavin derivatives through chemiluminescence and DNA damage analyses - Yuan-yuan Wu; Wei Li; Yi Xu; En-hui Jin; You-ying Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Synergistic effects of tea polyphenols and ascorbic acid on human lung adenocarcinoma SPC-A-1 cells - Wei Li; Jian-xiang Wu; You-ying Tu (Journal of Zhejiang University-SCIENCE B, 2010)

Isolation and molecular characterization of equine H3N8 influenza viruses from pigs in China - Jiagang Tu; Hongbo Zhou; Taozhen Jiang; Chun Li; Anding Zhang; Xuebo Guo; Wei Zou; Huanchun Chen; Meilin Jin (Archives of Virology, 2009)